PENETAPAN HARGA POKOK PRODUKSI PAKAIAN SERAGAM AKADEMI KEBIDANAN PERMATA HUSADA SAMARINDA PADA PENJAHIT SARTIKA EXPRESS SAMARINDA - Supriyatno, Andik (EKONOMIA, 2012)
Andik Supriyatno. The pricing of goods manufactured uniforms Midwifery Academy Husada Samarinda Jewel Express Tailors Sartika Samarinda (under the guidance of the mother and father of titin Ruliana and Imam Nazaruddin Latif). The purpose and this paper is to calculate the cost of goods manufactured uniforms Midwifery Academy Samarinda Jewel Husada full costing method in Tailor Sartika Express Samarinda. In accordance with the purpose of writing this, the principal issues raised: Is the determination of cost of goods manufactured uniforms Midwifery Academy Husada Samarinda Jewel Express Tailors Sartika higher than the base price set by the author using the full costing method in July 2011''? Based on these fundamental issues, the proposed hypothesis as follows: